The early bird catches the IL-2 in C-type lectin receptor-dependent activation of dendritic cells - Blamberg, Robert; Lang, Roland (Science Signaling, 2023)
The transcriptional response of macrophages and dendritic cells to stimulation of pattern recognition receptors can be unexpectedly distinct. In this issue of Science Signaling, Watanabe et al. demonstrate that IL-2 is differentially induced by the closely related C-type lectin receptors Dectin-2 and Mincle and reveal early signaling through the adaptor protein FcRγ as a critical mechanism.
CRIS-Team Scopus Importer:2023-03-24

Tuning of adaptive immune responses by TNF at the level of C-type lectin receptor expression - Blamberg, Robert; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27